A person-centred approach to understanding dark-side antecedents and students' outcomes associated with physical education teachers' motivation. (November 2021) - Franco, Evelia; Coterón, Javier; Gómez, Valeria; Spray, Christopher M.
Abstract: The present study firstly establishes physical education (PE) teachers' motivational profiles based on their autonomous motivation, controlled motivation and amotivation and, secondly, investigates how different PE teachers' motivational profiles differ in terms of certain maladaptive antecedents (i.e. psychological need frustration, pressures perceived at work and burnout). It also addresses the differences in their students' perception of autonomy support, psychological need satisfaction and autonomous motivation. A total of 105 PE teachers and their 2164 students completed validated questionnaires. Four profiles were retained in the cluster analysis. Results showed that teachers who were high on autonomous motivation displayed the most optimal pattern of outcomes, whereas teachers who were high on amotivation showed the opposite pattern. Analysis of the established profiles suggested that the experience of controlled motivation was linked with maladaptive outcomes among both teachers and students. Implications for educational policy and practice are discussed. Highlights: Physical education teachers' motivational profiles might provide interesting insights as for teachers' dark-side variables. 105 physical teachers and 2164 students taught by these teachers participated in the study. More motivation is not always better: the relevance of a qualitative view. Students seem to differ in terms of motivational outcomes according to their physical education teachers' profiles.